'Pregnant women voice their concerns and delivery method preferences during the COVID-19 pandemic in Turkey'. (2nd November 2022) - Çalık, Kıymet Yeşilçiçek; Küçük, Ebru; Beydağ, Kerime Derya
ABSTRACT: Objective: To evaluate pregnant women's voice their concerns and delivery method preferences during the COVID-19 pandemic in Turkey. Methods: A cross-sectional study is survey based using an online survey platform. Three hundred pregnant women were included between 16 May and 12 June 2020 in Turkey. Sociodemographic features, obstetric features, concerns about COVID-19, delivery method preferences, and Brief Measure of Worry Severity were evaluated. Results: It was determined that the concerns of pregnant women about the pandemic were moderate (12.73 ± 6.838) and did not alter their delivery method preferences. However, the concerns of the pregnant women who planned to perform their delivery by caesarean section before COVID-19 and whose delivery method preferences changed during the pandemic process were higher (p < 0.05). Additionally, during the COVID-19 period, pregnant women often harbour concerns such as 'not knowing how it would affect my baby if I have to take medications for COVID-19 (90.3%)' 'getting infected by COVID-19 during my pregnancy (89.7%)' 'not having a healthy pregnancy until birth (89%)'. Conclusions: Delivery method preferences of pregnant women did not change in the COVID-19 pandemic. On the other hand, COVID-19 pandemic is impacting on the pregnant women experiencing moderate concerns about their pregnancy, delivery, postpartum period, and their baby.